Biodegradable polyester-based nano drug delivery system in cancer chemotherapy: a review of recent progress (2021–2023) - Wang, Zongheng; Xiao, Miaomiao; Guo, Fangliang; Yan, Yue; Tian, Hong; Zhang, Qianshi; Ren, Shuangyi; Yang, Liqun (Frontiers in Bioengineering and Biotechnology, 2023)
Cancer presents a formidable threat to human health, with the majority of cases currently lacking a complete cure. Frequently, chemotherapy drugs are required to impede its progression. However, these drugs frequently suffer from drawbacks such as poor selectivity, limited water solubility, low bioavailability, and a propensity for causing organ toxicity.Consequently, a concerted effort has been made to seek improved drug delivery systems.Nano-drug delivery systems based on biodegradable polyesters have emerged as a subject of widespread interest in this pursuit. Extensive research has demonstrated their potential for offering high bioavailability, effective encapsulation, controlled release, and minimal toxicity. Notably, poly (ε-caprolactone) (PCL), poly (lactic-co-glycolic acid) (PLGA), and polylactic acid (PLA) have gained prominence as the most widely utilized options as carriers of the nano drug delivery system. This paper comprehensively reviews recent research on these materials as nano-carriers for delivering chemotherapeutic drugs, summarizing their latest advancements, acknowledging their limitations, and forecasting future research directions.